Statistical Analysis of Bifurcating Region 2 Field-Aligned Currents Using AMPERE - Sangha , H. K.; Milan , S. E.; Anderson , B. J.; Korth , H. (Frontiers in Astronomy and Space Sciences, 2022)
We present a statistical analysis of the occurrence of bifurcations of the Region 2 (R2) Field-Aligned Current (FAC) region, observed by the Active Magnetosphere and Planetary Electrodynamics Response Experiment (AMPERE). Previously, these have been shown to occur as the polar cap contracts after substorm onset, the beginning of the growth phase. During this phase both the Region 1 (R1) and R2 currents move equatorwards as the polar cap expands. Following onset, the R1 FAC region contracts polewards but the R2 FAC continues to expand equatorwards before eventually fading. At the same time, a new R2 FAC develops equatorwards of the R1 FAC. We have proposed that the bifurcated FACs formed during substorms are associated with plasma injections from the magnetotail into the inner magnetosphere, and that they might be the FAC signature associated with Sub-Auroral Polarization Streams (SAPS). We investigate the seasonal dependence of the occurrence of bifurcations from 2010 to 2016, determining whether they occur predominantly at dawn or dusk. Region 2 Bifurcations (R2Bs) are observed most frequently in the summer hemisphere and at dusk, and we discuss the possible influence of ionospheric conductance. We also discuss a newly discovered UT dependence of the R2B occurrences between 2011 to 2014. This dependence is characterized by broad peaks in occurrence near 09 and 21 UT in both hemispheres. Reasons for such a preference in occurrence are explored.